Alokatif Penggunaan Faktor-Faktor Produksi Usaha Pembesaran Ikan Patin di Kolam (Studi Kasus di Desa Banua Lawas Kecamatan Banua Lawas Kabupaten Tabalong) - Arief Hidayatullah; Siti Muhimah (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2014)
This study aims to determine the effect of (i) production factors on catfish production, (ii) production factors that have a significant effect and (iii) allocative efficiency level of the use of production factors to enlarge catfish in ponds in Banua Lawas Village Banua Lawas District, Tabalong Regency. Research and data collection was conducted by survey and interview methods with a sample of 28 respondents who were catfish enlargement pond entrepreneurs in Banua Lawas Village, Banua Lawas District, Tabalong Regency. The analysis used is the analysis of the Cobb-Douglas production function and allocative efficiency. The results showed that the F test stated that all variables in the area of ponds, seeds, feed, and labor simultaneously had a significant effect on the production of catfish. Based on the results of the coefficient of determination shows that 88% of the variation in the amount of production can be explained by the variable pool area, seeds, feed, and labor. While 12% is influenced by other variables not included in the regression model. The results of the t test state that the factors of seed, feed, and labor have a significant and significant effect on catfish production while the pool area factor has no significant and no significant effect on catfish production. The value of price efficiency (EH) of seeds, feed, and labor are respectively (14.1), (0.4), (4.3), which means that the use of production inputs is not allocatively efficient.